Performance analysis of hydrokinetic hybrid system with water velocity estimation technique for rural electrification in East Malaysia - Mohd Saupi, Almalik Faisel (2018)
The electricity coverage in Sarawak is the lowest compared to Sabah and Peninsular Malaysia at 78.74%, 82.5% and 99.62%, respectively. Majority of the population (84.4%) in the Kapit District, Sarawak resided in rural areas and mostly situated along the main riverbanks has great potential to generate electrical energy with a hydrokinetic system. Yearly water velocity data is the most significant parameter to perform a hydrokinetic analysis study. Nevertheless, the data retrieved from local river databases are inadequate for river energy analysis, thus hindering its progression. Instead, flow rates and rainfall data had been utilised to estimate the water velocity data. To date, there is still no study that has been found on estimating of water velocity data in unregulated river using water level. Therefore, a novel technique of estimating the daily average water velocity data in unregulated rivers is proposed. The modelling of regression equation for water velocity estimation on-site was performed. Two regression model equations were generated to estimate water level and water velocity on-site. They were proven to be valid as the Coefficient of Determination (R2) values 87.4% and 87.9%, respectively. The combination of both regression model equations can be used to estimate long term time series water velocity data for type-C unregulated river in rural areas. Six data sets of daily average water velocity data throughout the year was estimated on-site from 2010 to 2015 using 6 years of water level data taken from hydrological stations upstream. The Hydrokinetic-PV solar-Diesel-Battery hybrid system model was simulated using Hybrid Optimization Model for Renewable Electric (HOMER) software using six years of estimated water velocity data on-site. From the simulation results, it can be concluded that the Hydrokinetic-PV solar-Battery hybrid system is more economical than other hybrid systems. This is especially in terms of using 100% renewable energy resources with the lowest of Cost of Energy (COE). The COE of this hybrid system is 62% lower than the existing stand-alone diesel generator in any other state of the water velocity. However, if 10% of energy shortage is allowable per year, the COE of proposed hybrid system is 73% lower than COE of existing diesel generator. It clearly shows that the Hydrokinetic-PV solar-Battery hybrid system is the best solution for the remote school electrification and is able to eliminate the use of existing diesel generators.